Growth and yield parameters of cardamom (Elettaria cardamomum Maton) as influenced by nutrition and planting density - RAVINDRA MULGE, M M HOSMANI, V S KORIKANTHIMATH, RAJENDRA HEGDE (Journal of Spices and Aromatic Crops, 1998)
Investigations carried out on cardamom CElettaria cardamomum) at Appangala CKarnataka, India) to assess the effect of NPK nutrient combinations and planting densities on growth and yield parameters indicated that, increasing nutrient levels as well as planting density resulted in increased plant height at early stages of plant growth. Increased fertilizer levels increased number ofleaves and panicles, but increased planting density had adverse effect on these characters. A fertilizer combination of \50:75:300 kg NPKlha and 5000 plantslha planted at 2 m x 1 m spacing was comparatively optimum for satisfactory growth of cardamom.